Functional evaluation distinguishes MCI patients from healthy elderly people - The ADCS/MCI/ADL scale - Pedrosa, H. (2013)
Patients with MCI may present minor impairments in activities of daily living (ADL). The main objective of this work was to evaluate the ability of two versions of the Alzheimer's Disease Cooperative Study / Activities of Daily Living scale adapted for MCI patients (ADCS/MCI/ADL18 and ADCS/MCI/ADL24) to distinguish patients with MCI from healthy control subjects. Participants were 60 years or older and community dwelling: 31 control subjects, 30 aMCI patients and 33 AD patients. A protocol of neuropsychological tests, global evaluation scales, functional scales, and depressive symptoms assessment was used. Activities of balancing the cheque book, using a telephone, going shopping, taking medication regularly, finding objects, talking about current events, watching television, initiating complex activities, keeping appointments or meetings, reading, getting around outside the home and driving a car were impaired in aMCI patients. The ADCS/MCI/ADL24 scale was better than the ADCS/MCI/ADL18 scale in distinguishing aMCI patients from healthy controls (sensitivity=0.87, specificity=0.87, ROC c=0.887, cut-off point=52/53). The detection of initial functional changes with appropriate scales may contribute to the early diagnosis of MCI and the development of targeted interventions to improve everyday function or prolong independence.